PENGARUH PAJAK, RETRIBUSI DAN PENDAPATAN LAIN-LAIN YANG SAH TERHADAP PENDAPATAN DAERAH DI PEMERINTAH KABUPATEN TABANAN - I Nyoman Ariana Guna; I Dewa Gede Rastana Rastana; I Wayan Mula Sarjana Sarjana (Jurnal Ilmiah Satyagraha, 2023)
Many factors can affect regional income in the Tabanan Regency Government, one of which is taxes, levies and other legitimate income, so in this study it will be examined about the effect of taxes, levies and other legitimate income on regional income in the Tabanan Regency Government. .Based on data analysis, the results obtained (1) tax has a positive and significant effect partially on regional income in the Tabanan Regency Government, because the t-count value is greater than the t-table value (5.827 1.943) and the significance value is less than five percent (0.000 0.050 ), (2) retribution has a positive and significant effect partially on regional income in the Tabanan Regency Government, because the t-count value is greater than the t-table value (2.971 1.943) and the significance value is less than five percent (0.000 0.050), ( 3) Other legitimate income has a positive and significant partial effect on regional income in the Tabanan Regency Government, because the t-count value is greater than the t-table value (3.846 1.943) and the significance value is less than five percent (0.042 0.050) and (4) taxes, levies and other legitimate income have a significant simultaneous effect on regional income in the Taba Regency Government nan, because the calculated F value is greater than the table F value (34.009 4.760).To the Tabanan Regency government given the importance of regional income in carrying out regional development, it is hoped that the Tabanan Regency government should be able to optimize the potential of the region it has so that revenue from taxes, levies and other legitimate income can continue to increase in the future